1994
DOI: 10.1083/jcb.127.1.55
|View full text |Cite
|
Sign up to set email alerts
|

The alpha and beta subunits of the Na,K-ATPase can assemble at the plasma membrane into functional enzyme.

Abstract: Synthesis and assembly of most oligomeric plasma membrane proteins occurs in the ER. However, the role the ER plays in oligomerization is unknown. We have previously demonstrated that unassociated alpha and beta subunits of the Na,K-ATPase are targeted to the plasma membrane when individually expressed in baculovirus-infected Sf-9 cells. This unique property allows us to determine if assembly of these two polypeptides is restricted to the ER, or if it can also occur at the plasma membrane. To investigate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…For example, recent studies of exocrine gland cells using fractionation and phasepartitioning methods showed that upon physiological stimulation, pumps are being actively recruited to the basolateral plasma membrane from cytoplasmic structures (Mircheff et al 1989). Alternatively, subunits of Na¤-K¤-ATPase may assemble at the plasma membrane (DeTomaso, Blanco & Mercer, 1994). While the mechanism of differential Differential Na¤-K¤-ATPase expression J. Physiol.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies of exocrine gland cells using fractionation and phasepartitioning methods showed that upon physiological stimulation, pumps are being actively recruited to the basolateral plasma membrane from cytoplasmic structures (Mircheff et al 1989). Alternatively, subunits of Na¤-K¤-ATPase may assemble at the plasma membrane (DeTomaso, Blanco & Mercer, 1994). While the mechanism of differential Differential Na¤-K¤-ATPase expression J. Physiol.…”
Section: Discussionmentioning
confidence: 99%
“…These agents have been reported to increase Na,KATPase function via a variety of mechanisms. Gene transfer has been used to study Na,K-ATPase expression and subunit interregulation in mammalian cell lines (34,(44)(45)(46)(47)(48)(49). Increased mRNA expression and altered protein profiles have been noted in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, targeting of coronavirus coat proteins [50] and Golgi resident enzymes [51] correlates with oligomerization in the Golgi apparatus. Remodeling and assembly of ion channels, such as ENaC and Na-K ATPases, can occur in late secretory compartments and at the plasma membrane [52][53][54]. Another class of proteins that oligomerize in the Golgi apparatus are tetraspanins, such as CD9, CD63, CD81 and CD151 [55].…”
Section: Reviewmentioning
confidence: 99%